2020
DOI: 10.1515/ntrev-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of multilayer CrN coatings deposited by hybrid HIPIMS after oxidation treatment

Abstract: AbstractChromium nitride coatings prepared by physical vapour deposition (PVD) show high hardness, high strength and good thermal conductivity, which makes them useful for cutting and forming tools. In this article, the microstructure and corrosion resistance of multilayer Cr/CrN coatings deposited by arc evaporation and hybrid high power impulse magnetron sputtering (hybrid HIPIMS) after oxidation between 500 and 800°C were examined. The average thickness of the coatings was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The authors concluded that the Nb-bearing samples had more compact and firm corrosion product films than the Nb-free samples. These thin layers of compounds form on the surface of a metal when it corrodes and act as a natural defense mechanism, establishing a barrier between the metal and the corrosive environment through the composition of various corrosion products, like oxides, hydroxides, and salts [98]. The integrity and compactness of these films are crucial in determining the metal's corrosion resistance, with more compact films offering greater resistance to ion migration and thus diminishing the extent of corrosion-induced destruction [99].…”
Section: Effects Of Corrosion On Weld Integritymentioning
confidence: 99%
“…The authors concluded that the Nb-bearing samples had more compact and firm corrosion product films than the Nb-free samples. These thin layers of compounds form on the surface of a metal when it corrodes and act as a natural defense mechanism, establishing a barrier between the metal and the corrosive environment through the composition of various corrosion products, like oxides, hydroxides, and salts [98]. The integrity and compactness of these films are crucial in determining the metal's corrosion resistance, with more compact films offering greater resistance to ion migration and thus diminishing the extent of corrosion-induced destruction [99].…”
Section: Effects Of Corrosion On Weld Integritymentioning
confidence: 99%
“…The findings indicated that CrN coatings prepared through the use of HIPIMS exhibited superior corrosion current and voltage under NaCl solution. Additionally, Zhu et al prepared a multilayer Cr/CrN coating using arc evaporation and hybrid HIPIMS, and they compared the microstructure and corrosion resistance of the films [21]. The majority of studies focusing on the corrosion resistance of the coatings rely on potentiodynamic polarization tests.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages they can bring, only a few authors have used these modern electrochemical techniques to characterize metallic materials coated with chromium nitride layers used under special conditions [ 40 , 41 , 42 ], and extremely few [ 43 , 44 ] have studied the behaviour of the coating and the oxides formed on their surface.…”
Section: Introductionmentioning
confidence: 99%